Towards a Comprehensive Procedure for Developing Measurement Scales for Cross-Cultural Management Research - Caramelli, Marco; van de Vijver, Fons (Management international / International Management / Gestiòn Internacional, 2013)
A procedure for developing and testing measurement scales for use in cross-cultural comparative management research is described. The procedure emphasizes the combination of adequate instrument design if a new instrument is used or adequate adaptation procedures if working with an existing instrument and state-of-the-art statistical analyses (notably multigroup confirmatory factor analysis) to test the adequacy of the scales in all groups. The procedure is illustrated in a study of competitive orientation among French, Mexican, US and Italian employees of multinational corporations.